PERJANJIAN PERDAMAIAN DOHA DIALOGUE ANTARA AFGHANISTAN-AMERIKA SERIKAT DAN TALIBAN DI ERA KEPEMIMPINAN ASHRAF GHANI - Ali Zhafir Talmullah (2022)
The conflict in Afghanistan is the aftermath of foreign occupation of the land. The United States and Afghanistan have always tried to eliminate the violence that occurred in Afghanistan by attacking the Taliban militia. The conflict that took place in Afghanistan resulted in a long war that caused many casualties on the land. Supported by many extremist wing groups, the Afghan government has limited weapons and security assistance. Thus, the Taliban have a great opportunity to stage a coup against the government under Ashraf Ghani. This research is discussed to see the extent of the peace process in Afghanistan during the leadership of President Ashraf Ghani. The dynamics of conflict resolution in Afghanistan is a special focus for the author because it causes many victims to fall. The conflict involving the United States, Afghanistan and the Taliban that has lasted more than 20 years will be resolved by an agreement based on the concepts that I will use. The author will use the concept of cooperation, conflict resolution and the concept of conflict as an effort to see the strengths of the three parties. The descriptive qualitative research method will answer and explain the alignments of the agreement and its realization towards peace building in Afghanistan. As for the results obtained from this study, the Doha agreement is seen as not encouraging a significant peace process.